(untitled) (Journal of the College of Education for Women, 2019)
The world’s renewable energy sources have taken on great importance, for its cleanness and its environmental effects as well as being a renewable source, Increased demand for fossil energy sources is also causing global warming and climate change. Iraq is an appropriate area for renewable energy This study shows that renewable alternative energy has not been used sufficiently enough at present. But this energy can play an important role in the future of renewable energy in Iraq. This research aims to study the renewable energy in Iraq (solar energy) and it is appropriate to develop this alternative energy for crude oil, which is characterized by the use of the most appropriate and less economical and more environmentally friendly. Solar energy is the most suitable alternative among these solutions because Iraq’s atmosphere is characterized by a large number of solar clocks during the 12 months of the year. The winter season is also characterized by high solar days, rainy and cloudy days, as well as easy installation of the solar system. All of these factors lead to a result that makes solar energy the first alternative energy alternative after crude oil in Iraq.